Patient-Reported Outcomes: Quality of Care on a Neurosurgical Ward. Issue 3 (11th July 2021) - Sadrameli, Saeed S.; Chan, Tiffany M.; Vaziri, Sasha; Murad, Gregory J. A.; Hooten, Kristopher G.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Objectives: Patient experience has become a quality measure in hospitals across the United States. To improve our understanding of our neurosurgical patient populationʼs satisfaction needs, we undertook a detailed survey to identify areas of needed improvement. Methods: Upon institutional review board approval, a detailed survey adopted from the Swedish quality-of-care patient questionnaire was distributed to all patients being discharged from the neurosurgical ward over a month period. From June 2014 to July 2014, all patients admitted to the neurosurgery service through the emergency department, clinic, or other facilities were enrolled. There were no specific inclusion criteria except for age older than 18 years, intact cognition to complete the survey, and return of a completed survey. Data were collected in 6 major categories, including information availability, patient accessibility, treatment received, caring perception, hospital environment, and overall satisfaction. Patients were evaluated by age, gender, surgery, and admission type. Results: Our analysis demonstrated an improved overall satisfaction in those patients being admitted electively from the clinic as compared with emergency department admissions or hospital transfers. In addition, patients admitted on an emergent basis reported a lower satisfaction pertaining to receiving information, specifically test results. Conclusions: Emergent admissions represent a subpopulation that may require additional strategies to improve patient satisfaction survey scores.